2019
DOI: 10.1007/s40430-019-2130-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical and tribological properties of hybrid green eggshells and graphite-reinforced aluminum composites

Abstract: Low cost, low density and good thermal stability of hens' eggshells make them a new reinforcement material. Further, eggshell (Es) is considered as a renewable eco-friendly material. Besides, its waste causes insect infestation and therefore pollution problems. Graphite (Gr) is one of the most commonly used reinforcements due to its self-lubricating properties. Hence, the current work aims to use the powder metallurgy technique to fabricate various aluminum matrix composites having different weight percentages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…However, these types of matrices are often characterized by low hardness and limited tribological properties, which limits their possible application. Hence, there is still a need to create metal-based composites reinforced with appropriate agricultural fillers, enhancing both mechanical and tribological properties of the produced materials [ 2 ]. All of the studied metal matrix composites reinforced with agricultural waste materials are presented in Table 1 .…”
Section: Agricultural Waste Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these types of matrices are often characterized by low hardness and limited tribological properties, which limits their possible application. Hence, there is still a need to create metal-based composites reinforced with appropriate agricultural fillers, enhancing both mechanical and tribological properties of the produced materials [ 2 ]. All of the studied metal matrix composites reinforced with agricultural waste materials are presented in Table 1 .…”
Section: Agricultural Waste Materialsmentioning
confidence: 99%
“…Among various metal materials used for tribological applications, aluminum and its alloys are one of the most commonly studied. However, these types of materials are characterized by low hardness and limited tribological properties, which, in turn, limit the possibilities of their application [ 2 ]. The most popular way to increase the strength of aluminum and its alloys is to add insoluble reinforcement to create a metal matrix composite.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, wear rate decreased with increasing RHA content in composites for all ranges of varying RHA size. Alomani et al 40 investigated the mechanical/tribological properties of green hybrid aluminium composites reinforced with eggshells and graphite particles wherein the researchers reported that maximum hardness and compression strength was exhibited by hybrid composite with 3 wt% of eggshells and these properties decreased as the concentration of eggshells increased up to 9 wt%. Also, mass loss in hybrid composites varied directly with weight percentage of graphite irrespective of weight percentage of eggshells.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that composites containing 3 wt.% B 4 C and 7 wt.% fly ash has higher hardness, tensile strength and wear resistance than unreinforced alloy. Almomani et al 18 found that eggshells (ES) and graphite (Gr) reinforced Al-based hybrid composites have higher compressive strength, hardness, and wear resistance than single reinforced composites. Durowoju et al 19 evaluated the mechanical properties of hybrid Gr-Al composites incorporated with ES, Si, and SiC particles.…”
Section: Introductionmentioning
confidence: 99%